2020
DOI: 10.5194/amt-2020-79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating mean molecular weight, carbon number, and OM/OC with mid-infrared spectroscopy in organic particulate matter samples from a monitoring network

Abstract: Abstract. Organic matter (OM) is a major constituent of fine particulate matter which contributes significantly to degradation of visibility, radiative forcing, and causes adverse health effects. However, due to its sheer compositional complexity, OM is difficult to characterize in its entirety. Mid-infrared spectroscopy has previously proven useful in the study of OM by providing extensive information about functional group composition with high mass recovery. Herein, we introduce a new method for obtaining a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…We also found that the primary WB and CC aerosols have similar mass spectra to the BBOA and HOA factors, respectively, and OH-aged OAs of both sources are similar to the SV-OOA factor. Furthermore, the spectral variations are consistent with our functional group analysis via FTIR, suggesting that the AMS mass spectra maintain some functional group and source class information even after aging and in spite of the extensive fragmentation (discussed further by Yazdani et al, 2021a). However, even at the moderate levels of aging of this work, a part of this information only exists in higher PCs, which explain the lower variance in the data (e.g., PC2 explains 12 % of the variance across source classes and oxidative aging studied in this work and distinguishes OH-aged CC and NO 3 -aged WB).…”
Section: Comparison Between Ams Mass Spectra and Fg Composition Of Oasupporting
confidence: 82%
See 1 more Smart Citation
“…We also found that the primary WB and CC aerosols have similar mass spectra to the BBOA and HOA factors, respectively, and OH-aged OAs of both sources are similar to the SV-OOA factor. Furthermore, the spectral variations are consistent with our functional group analysis via FTIR, suggesting that the AMS mass spectra maintain some functional group and source class information even after aging and in spite of the extensive fragmentation (discussed further by Yazdani et al, 2021a). However, even at the moderate levels of aging of this work, a part of this information only exists in higher PCs, which explain the lower variance in the data (e.g., PC2 explains 12 % of the variance across source classes and oxidative aging studied in this work and distinguishes OH-aged CC and NO 3 -aged WB).…”
Section: Comparison Between Ams Mass Spectra and Fg Composition Of Oasupporting
confidence: 82%
“…After baseline correction and blank subtraction, the multiple peak-fitting algorithm described by Takahama et al (2013) and implemented by Reggente et al (2019b), functioning based on nonlinear least squares analysis, was applied to the spectra to obtain major FG abundances of aCOH, COOH, aCH, and naCO (Yazdani et al, 2021a). The RONO 2 group abundances were not quantified due to the extensive overlap of its absorbances with other compounds and in order to keep the MIR estimates consistent with those of AMS, for which only total (organic plus inorganic) nitrate was estimated.…”
Section: Quantifying Organic Functional Groupsmentioning
confidence: 99%
“…However, ξ OM vary among the sampling events as indicated by the large standard deviations of average values. MW OM may not also be constant (240 g/mol) . This may further contribute to the discrepancy between measured and modeled f g values.…”
Section: Resultsmentioning
confidence: 99%
“…Two basic assumptions of K OA based models are ξ OCT /ξ OM and MW OCT /MW OM = 1 (eqs 2 and 3). A recent study by Yazdani et al 59 indicated that average MW of atmospheric OM range between 200 (rural) and 240 (urban) g/mol. Octanol has a MW of 130.23 g/mol, therefore MW OCT /MW OM could be ∼0.54 in an urban atmosphere.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation